Papel moderador do tipo de produto na relação entre traços de personalidade e comportamento de compra online : uma aplicação do modelo hierárquico de Mowen - Bento, Fernando Chiabai (2016)
This research aimed to investigate the previous factors of online buying behavior through the personality hierarchical model presented by Mowen (2000) for his Metatheoric Model of Motivation and Personality (3M), verifying if the type of the offered produ